Pauker, Guy J., et al., Diversity and Development in Southeast Asia: The Coming Decade, 1980s Project/Council on Foreign Relations, McGraw-Hill Book Company, 1977, 191 pp. - T. C., J. (Estudios de Asia y África, 1978)
-